2021
DOI: 10.1186/s40634-021-00415-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of dual Platelet-Rich Plasma (PRP) and Hyaluronic Acid (HA) therapy with PRP-alone therapy in the treatment of knee osteoarthritis: a systematic review and meta-analysis

Abstract: Purpose This study aims to compare the efficacy of a dual therapy of Platelet-Rich Plasma (PRP) and Hyaluronic Acid (HA) compared with PRP-alone therapy in the treatment of knee osteoarthritis (KOA). Methods PubMed, Embase, CINAHL, SCOPUS, Cochrane Library, grey literature and bibliographic references were searched from inception to January 2021. Only randomized controlled trials (RCTs) and retrospective cohort studies comparing the effect of PRP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Zhao et al found that compared with PRP alone, PRP + HA may have better clinical efficacy in the treatment of KOA [ 52 ]. Aw et al found that compared with PRP alone, PRP + HA may be effective at providing pain relief and improvement in function up to 1 year following administration in the treatment of KOA [ 53 ]. However, there was a discrepancy between our conclusions and theirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al found that compared with PRP alone, PRP + HA may have better clinical efficacy in the treatment of KOA [ 52 ]. Aw et al found that compared with PRP alone, PRP + HA may be effective at providing pain relief and improvement in function up to 1 year following administration in the treatment of KOA [ 53 ]. However, there was a discrepancy between our conclusions and theirs.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular injection therapy is recognized as a feasible non-operative treatment of KOA and traditionally included hyaluronic acid (HA) or glucocorticoid as means of promoting joint lubrication, reducing joint inflammation, and reducing pain [ 5 7 ]. Recently, clinicians have treated KOA with intra-articular injections of hyaluronic acid (HA), platelet-rich plasma (PRP) and bone marrow concentrate (BMAC) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis (OA) is the most recognized form of OA, responsible for approximately 4/5th of the global burden of the OA [ 1 ]. The prevalence of knee OA has continued to increase over the last few decades with no indications of deceleration [ 1 ].…”
mentioning
confidence: 99%
“…Knee osteoarthritis (OA) is the most recognized form of OA, responsible for approximately 4/5th of the global burden of the OA [ 1 ]. The prevalence of knee OA has continued to increase over the last few decades with no indications of deceleration [ 1 ]. Its pathophysiology involves synovial tissue inflammation and articular cartilage deterioration, leading to debilitating pain and loss of function [ 2 , 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation